DETERMINAN KETERLIBATAN KERJA UNTUK TERCAPAINYA PERILAKU INOVATIF - Irene Wirjadi (Jurnal Manajemen dan Pemasaran Jasa, 2014)
The background of this study was to investigate the innovative behavior of service firms (education) in order to determine whether role benefit, job autonomy and strategic attention would affect work engagement of the teachers and their innovative behavior on teaching.Data analysis used in this study was using the Linier Regretion with Ordinary Least Squares Method. The respondents in this study were primary school teacher of Sekolah Kristen Ipeka in Jakarta.The result of this study concluded that role benefit and strategic attention have positive relationship with teacher engagement, but job autonomy has a negative relationship with teacher engagement. On the other hand, teacher engagement has a positive relationship with innovative behavior.Key words: strategi manajemen, keterlibatan kerja, perilaku inovatif, guru